The effect of different types of mulch and different cultivation methods on the quantitative and qualitative traits of sunflower (Helianthus annuus L.) in Ahvaz climate - Rezvan Kazemi Hasanvand; Amin Lotfi Jalal-Abadi; Alireza Abdali Mashhadi; Ahmad Kochekzadeh; Abdolreza Siyahpoosh (Journal of Central European Agriculture, 2023)
To investigate the effect of mulch and different cultivation methods on the quantitative and qualitative yield of oil sunflower (Helianthus annuus L.) in Ahvaz climate, a factorial experiment in randomized complete blocks with three replications in the 2017-2018 crop year was in the research farm of Agricultural Sciences and Natural Resources University of Khuzestan. The first factor includes different types of mulch in five levels (non-application, wheat straw, white plastic, live mulch (mung bean cultivation), and black plastic) and the second factor includes three-level cultivation method (on a flat surface, ridge cultivation, and inside the furrow cultivation). The results showed that in the flat surface and on the ridge, black plastic produced the highest amount of chlorophyll a, b, and In the inside the furrow, the highest chlorophyll a was obtained in the application of living mulch. The highest grain yield and oil yield were obtained from the interaction of wheat straw mulch × in the furrow and wheat straw mulch on the ridge. In addition, the highest harvest index was obtained in the treatment of white plastic mulch on a flat surface with an average of 51.85%. In general, it can be said that the treatment of wheat straw and straw × in the inside the furrow and wheat straw × on the ridge were superior in terms of quantitative and qualitative performance.